Reduced contrast agent volume using a heart-rate dependent and free-breathing scanning protocol in coronary computed tomography angiography (CTA) for patients with chronic obstructive pulmonary disease (COPD) - Zengkun Wang; Guoyue Chen; Dewei Song; Xiaodie Xu; Chu Chu; Shuning Zhang; Huijing Chai; Hairong Yu; Xiaomei Luan; Peiji Song (BMC Cardiovascular Disorders)
Abstract Background The personalized, free-breathing, heart rate-dependent computed tomography angiography (CTA) protocol can significantly reduce the utilization of contrast medium (CM). This proves especially beneficial for patients with chronic obstructive pulmonary disease (COPD) undergoing coronary artery CTA examinations. Objective The aim of this study was to evaluate the feasibility of a personalized CT scanning protocol that was tailored to patients’ heart rate and free-breathing for coronary CTA of patients with COPD. Methods A total of 400 patients with COPD who need to undergo the coronary CTA were prospectively randomized into two groups (patients with vascular occlusion were excluded). Group A (n = 200) underwent CTA following a traditional protocol (70mL). The timing of the scans in Group B (n = 200) was determined according to the patient’s HR and free-breathing (30mL). Results No difference was found between the two groups in the CT values of RCA, LA, or LCX; (p = 0.131, 0.195 and 0.116). Subjective ratings of image quality (Table 2) were not statistically different between the two groups (p = 0.825). Conclusion By adopting a heart-rate dependent and free-breathing protocol, the contrast medium volume were reduced in coronary CTA for patients with COPD, while the image quality was remained comparable to those acquired with routine CTA protocol.